From Collective Tradition to National Integration: Reconstructing Mutual Cooperation through the Astagatra Perspective - Nina; Adipa Parawita; Jacky Wardhana; Ratih Purwanti; Reza Ibnu Syakirin (Jurnal Pendidikan Sosial Indonesia, 2026)
Mutual cooperation (gotong royong) remains an important socio-cultural practice within Indonesian rural communities despite increasing modernization and changing social lifestyles. This study examines the forms of gotong royong practices in Pinang Luar Village, their contribution to national integration through the Astagatra perspective, and the factors influencing their sustainability. The research employed a descriptive qualitative case study approach involving one neighborhood head and four village residents selected purposively. Data were collected through in-depth interviews, direct observation, and documentation, and analyzed using thematic analysis. The findings reveal that collective activities such as river cleaning, cemetery maintenance, roadside cleaning, and environmental management continue to strengthen social interaction, solidarity, and communal responsibility among residents. The study further demonstrates that gotong royong contributes to socio-cultural resilience, implementation of Pancasila values, and community-based social integration within the Astagatra framework. However, modernization and declining youth participation increasingly challenge the sustainability of collective traditions. Gotong royong masih menjadi praktik sosial-budaya penting dalam masyarakat pedesaan Indonesia di tengah modernisasi dan perubahan gaya hidup sosial. Penelitian ini bertujuan menganalisis bentuk-bentuk praktik gotong royong di Desa Pinang Luar, kontribusinya terhadap integrasi nasional dalam perspektif Astagatra, serta faktor-faktor yang memengaruhi keberlanjutannya. Penelitian menggunakan pendekatan studi kasus kualitatif deskriptif dengan melibatkan satu Ketua RT dan empat warga desa yang dipilih secara purposif. Data dikumpulkan melalui wawancara mendalam, observasi langsung, dan dokumentasi, kemudian dianalisis menggunakan analisis tematik. Hasil penelitian menunjukkan bahwa kegiatan seperti pembersihan sungai, pemeliharaan makam, pembersihan jalan, dan pengelolaan lingkungan masih memperkuat interaksi sosial, solidaritas, dan tanggung jawab kolektif masyarakat. Penelitian ini juga menunjukkan bahwa gotong royong berkontribusi terhadap ketahanan sosial-budaya, implementasi nilai-nilai Pancasila, dan integrasi sosial berbasis komunitas dalam kerangka Astagatra. Namun, modernisasi dan menurunnya partisipasi generasi muda menjadi tantangan terhadap keberlanjutan tradisi kolektif masyarakat.